Atrocalopteryx auco spec. nov. from Vietnam, with taxonomic notes on its congeners (Odonata: Calopterygidae) - Hämäläinen, Matti (Zootaxa, 2014)
Atrocalopteryx auco Hämäläinen, spec. nov. (holotype ♂, from Vietnam, Lang Son province, Huu Lien, Tan Lai, alt.      260 m, 9 June 2008, deposited at RMNH, Leiden, The Netherlands) is described and illustrated for both sexes and compared with other species in the genus. The new combination Atrocalopteryx laosica (Fraser, 1933), comb. nov. is made. An annotated list of Atrocalopteryx species and keys to both sexes are presented. Male of A. auco differs from the other two completely opaque-winged species (A. atrata and A. atrocyana) by having yellowish crossveins on the under surface of the wings and by having the underside of abdominal segments 8–10 strikingly yellowish. The female of A. auco can be easily separated from A. atrata  and A. atrocyana  by the presence of whitish pseudopterostigma in both wings. Problems in the definition of the genus Atrocalopteryx are discussed.